Double inversion recovery in evaluation of multiple sclerosis: a narrative review - Al-Mutairi, Abdullah Dhaifallah; Mahmud, Rozi; Suppiah, Subapriya; Abu Hassan, Hasyma (Sociedad Latinoamericana de Hipertension, 2019)
Double Inversion Recovery (DIR) is an accurate method used to evaluate the Multiple Sclerosis (MS). There are also other techniques suggested for this purpose, but those are not as accurate as DIR. It is important because it could be helpful to diagnose the patients with MS in early stages and it makes the therapists able to start the therapy process in right time. This fact is accepted, but there is a lack of researches about it and still there is a need to other researches with clear methodology. This narrative review aimed to have a look on previous studies done about DIR.